Integration of knowledge between Arabic sciences: structuring of the text and its role - Abdel Maqsud Sayed Ahmed, Mohamaed Aziz; Md. Noor, Mohamad Lukman Al Hakim; Mohd Ghalib, Mohd Feham (UKM Press, 2024)
The construction of the text undoubtedly affects the knowledge integration of its parts and diversion between a fragmented reading text, and a single weft text reading. This is a reading that takes into account all aspects of the text, and that is a reading that looks into part of the text without taking into account all aspect of it. And, consequently, knowledge integration varies according to our view of the text, we need to pay attention to a comprehensive and varied reading of the texts! So that we do not read the texts when we lose their rhythm, their pomp and their greatness by focusing on one aspect only and neglecting several aspects have a great impact on the text's appearance in a new diverse format. Let us imagine the text of an audio, morphological, grammatical, semantic, rhetorical, literary, or ‘arudh, and another text reading at all these levels, how would its knowledge integration be? This is what this research will demonstrate by analysing several selected texts through which to demonstrate how the text's holistic view plays an important role in knowledge integration. With a view to demonstrating the complementary relationship between Arabic sciences and its impact on the meaning, following the analytical approach in clarifying this, by presenting and analysing some texts in an integrated linguistic analysis, the conclusion is that taking into account the knowledge integration of Arabic sciences in reading and analysing texts has a major role to play in demonstrating its textual coherence, its comprehensiveness and its diversity. We will address this by describing the concept of knowledge integration, as well as the science of Arabic, and by referring to certain terms of text linguistics and their role in how to read texts that maintain the integrity of their aspect and the diversity of their meanings